Evolution of the MSBS Grot Assault Rifle from Version A0 to Version A2 - Ryszard B. WOŹNIAK (Rozwój karabinka MSBS GROT od wersji A0 do wersji A2, 2021)
On 15 December 2017, Fabryka Broni “Łucznik”- Radom Sp. z o.o. (FB Radom), a subsidiary of Polska Grupa Zbrojeniowa S.A., delivered the first batch of 1,000 MSBS Grot C 16 FB M1 calibre 5.56 mm standard (basic) assault rifles (version A0) to the Polish Territorial Defence Force and thus initiated the process of deployment of the assault rifle in the Polish Armed Forces. MSBS Grot was developed by Polish design and process engineers at FB Radom and the Military University of Technology (MUT, Warsaw, Poland) who by mediation of the proper Armament Acquisition and Development Department collected the improvement suggestions and operational feedback from 2.5 years of testing by operators from the armed forces. The suggestions and feedback were thoroughly analysed and discussed during periodic meetings attended by the representatives of the Territorial Defence Force (TDF) Command, the Special Forces Component Command, the 3rd Regional Military Representation (RMR), MUT, and FB Radom. Based on the conclusions from the testing period and the results of theoretical and instrumental testing of the solutions proposed for implementation, the MSBS Grot assault rifles show systematic improvements up to the current version, A2. This paper presents the design of the MSBS Grot Version A0 assault rifle and the construction and processing modifications for version A1 and version A2. During the optimisation effort backed by theoretical and instrumental testing, there was special focus on the assurance of high operating safety and reliability, plus the required ergonomics of the assault rifle under various operating conditions. The paper also presents the avenues for further potential improvements of MSBS Grot.
Keywords: Konstrukcja broni strzeleckiej